The critical transition from junior to elite football: Resources and barriers - Chamorro, J. L.; Sánchez-Oliva, D.; Pulido, J. J. (Football Psychology - From Theory to Practice, 2019)
The popular idea that it is quite difficult to become a professional soccer player is well known by all persons involved in any way in the world of soccer. According to the Federation Internationale de Football Association (FIFA), more than 265 million people play football around the world. With these numbers we can imagine the quantity of children that play soccer, slowly moving up in categories with the dream of making the transition into the elite of this sport one day. In the last decade, researchers have developed theoretical models and studies about how to understand the athlete in this transition and to explore what factors have influence in the process of adaptation to professional sport. This chapter will review the different theoretical frameworks used to explore this transition to professional sport through three different categories (Alfermann & Stambulova, 2007): (a) career development descriptive models, (b) career transitions explanation models, and (c) career transitions intervention models. In addition, we will discuss the main conclusions reached by the works that have studied this transition and those factors that influence the performance and well-being of young elite athletes following the suggestion of Bruner, Munroe-Chandler, and Spink (2008), which classified barriers and resources transition on and off the field, with particular emphasis on soccer. Finally, we will discuss the practical implications of these results accompanied by recommendations for young soccer players, coaches, families, and clubs on how to act to try to make the adjustment to professional soccer as successful as possible.